Sidagro Development: An Experience Report on the Partnership between the Federal University of Lavras and the Agricultural Institute of Minas Gerais - Lopes, Lucas Alvarenga; Durelli, Rafael Serapilha; Terra, Ricardo (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2025)
This article presents an experience report on the development of Sidagro Web, a governmental system developed through a partnership between the Federal University of Lavras (UFLA) and the Agricultural Institute of Minas Gerais (IMA), with a primary focus on software quality assurance. The report details key architectural and technical decisions that guided the project throughout its lifecycle, providing the rationale for each choice and emphasizing their contributions to enhancing system quality. The discussion is organized into five main categories: (i) high-level architectural choices, including layered separation and foundational technologies; (ii) backend-specific decisions, such as exception handling, object mapping, auditing mechanisms, and code conventions; (iii) frontend considerations, including form validation and dynamic data handling; (iv) infrastructure-related strategies, covering environment setup, CI/CD pipelines, and DevOps tooling; and (v) documentation and version control practices, which are applied transversally across all project dimensions. We demonstrate that the systematic adoption of these practices significantly improved the system’s robustness, maintainability, and long-term sustainability, offering valuable insights for similar large-scale software projects with stringent quality requirements.